Alam Pikir Populis Islam dan Merebaknya Histeria Massa: Potret Pergeseran Nilai Kebenaran dan Memudarnya Ideologi - Purnama, Fahmy Farid (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
This study analyzes the phenomenon of Islamic populism, the nature of populist thought and its relation to mass hysteria. Global political events involving large numbers of masses have put the study of populism shifting from the periphery to the center of attention. In its various manifestations, populism represents a rejection of political elites which is based on the argument that populism is a response to a crisis of legitimacy for political institutions and actors. Based on descriptive and critical content analysis, this study aims to examine the trend of populism at the level of digital culture which is dominated by spectacle and market culture. By investigating how populist thinking works, this research seeks to understand the dynamics of populism and the logical consequences it entails, especially regarding the future of the actual heterogeneity of society, both in religious and cultural contexts, behind its tendency to totalize and homogenize everything through the logic equivalent in populism.